Checking RTECTL properties of STSs via SMT-based Bounded Model Checking - Zbrzezny, Agnieszka; Zbrzezny, Andrzej (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
We present an SMT-based bounded model checking (BMC) method for Simply-Timed Systems (STSs) and for the existential fragment of the Real-time Computation Tree Logic. We implemented the SMT-based BMC algorithm and compared it with the SAT-based BMC method for the same systems and the same property language on several benchmarks for STSs. For the SAT- based BMC we used the PicoSAT solver and for the SMT-based BMC we used the Z3 solver. The experimental results show that the SMT-based BMC performs quite well and is, in fact, sometimes significantly faster than the tested SAT-based BMC.
Keywords: RTECTL; STS; SMT; IJIMAI